2011
DOI: 10.4236/fns.2011.28119
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status and School Achievements in a Rural Area of Anti-Atlas, Morocco

Abstract: Nutritional status is the best indicator of the global well-being of children. However, malnutrition affects physical growth, cognitive development, physical work capacity, and it consequently influences human performance and health. The present study was designed to identify factors that may influence the nutritional status and educational achievements of the children in a rural area of ANTI Atlas of Morocco. The nutritional status of 162 children (12 to 15 years of age) was assessed by nutritional anthropome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
4
5
1
2
Order By: Relevance
“…Children who have mothers with secondary and above educational status have more than two times higher English, Amharic, and average semester scores given that all of the other variables in the model are held constant. This study finding is similar with a study done in Morocco, Malaysia, Iran, and Hawa Gelan, Southwest Ethiopia [15,[19][20][21]. This signifies the importance of educating females in improving the child nutritional status as well as academic achievement.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Children who have mothers with secondary and above educational status have more than two times higher English, Amharic, and average semester scores given that all of the other variables in the model are held constant. This study finding is similar with a study done in Morocco, Malaysia, Iran, and Hawa Gelan, Southwest Ethiopia [15,[19][20][21]. This signifies the importance of educating females in improving the child nutritional status as well as academic achievement.…”
Section: Discussionsupporting
confidence: 90%
“…This difference could be due to the sociodemographic and geographic differences. The magnitude of stunting in this study is greater than the study done in a rural area of Morocco which was 22.8% [19].…”
Section: Discussioncontrasting
confidence: 73%
“…This is consistent with what is observed in the literature since, also noted that there is no significant relationship between academic achievement of children and their nutritional status [14]. Grantham-McGregor, et al by cons reviewed the literature and found that early stunting (HAZ < -2 SD from median) and poverty in the first five years of life were associated with lower subsequent cognitive abilities, school achievement, and productivity in adult life [16].…”
Section: Mean ± Standard Deviation Parameterssupporting
confidence: 83%
“…Possible explanations are the lack of adequate complementary infant feeding both quantitatively and qualitatively. It also appears that the transition to family meals is not always beneficial to the child and that food diversification is associated with the growth of children [14]. We note respectively 30.1% of girls and 38.7% of boys rated as poor for math and 17.1% of girls and 37.3% of boys rated as poor to average, so boys appear less successful than girls.…”
Section: Mean ± Standard Deviation Parametersmentioning
confidence: 64%
“…The focus of health education is to teach the skills that enable students to make healthy choices and avoid health-risk behaviours [14]. Poor health related behaviours, as well as malnutrition and limited knowledge about nutrition have been reported in studies conducted among Moroccan adolescents [12, 15, 16]. A study conducted in Morocco, evaluating the content of school textbooks in relation to health lessons, concluded that the lessons in these textbooks are inadequate, inaccurate, or out of date, and hence need improvement [17].…”
Section: Introductionmentioning
confidence: 99%